Impact of "half-crown/two carbonyl"–Ca2+ metal ion interactions of a low molecular weight gelator (LMWG) on its fiber to nanosphere morphology transformation with a gel-to-sol phase transition. Issue 28 (4th July 2018) - Maity, Arunava; Dey, Ananta; Si, Mrinal Kanti; Ganguly, Bishwajit; Das, Amitava
Abstract : We report here a smart functional low molecular weight gelator (LMWG)L, containing an unusual metal ion coordination site, i.e. "half-crown/two carbonyl" . Abstract : We report here a smart functional low molecular weight gelator (LMWG)L, containing an unusual metal ion coordination site, i.e. "half-crown/two carbonyl" . The gelatorL shows excellent gelation behavior with typical fibrillar morphology in acetonitrile, methanol and ethanol media. Upon Ca 2+ ion binding with its "half-crown/two carbonyl" coordination site, the acetonitrile gel ofL exhibits a fiber to nanosphere morphology transformation along with a gel-to-sol phase transition as confirmed by microscopic investigation and by direct naked eye visualization, respectively. The mechanism involved in this morphology transformation and gel-to-sol phase transition process was studied thoroughly with the help of computational calculations and various spectroscopic experiments and discussed.